Workflow for the Validation of Geomechanical Simulations through Seabed Monitoring for Offshore Underground Activities - Christoforos Benetatos; Felice Catania; Giorgio Giglio; Candido Fabrizio Pirri; Alice Raeli; Luciano Scaltrito; Cristina Serazio; Francesca Verga (Journal of Marine Science and Engineering, 2023)
Underground fluid storage is gaining increasing attention as a means to balance energy production and consumption, ensure energy supply security, and contribute to greenhouse gas reduction in the atmosphere by CO2 geological sequestration. However, underground fluid storage generates pressure changes, which in turn induce stress variations and rock deformations. Numerical geomechanical models are typically used to predict the response of a given storage to fluid injection and withdrawal, but validation is required for such a model to be considered reliable. This paper focuses on the technology and methodology that we developed to monitor seabed movements and verify the predictions of the impact caused by offshore underground fluid storage. To this end, we put together a measurement system, integrated into an Autonomous Underwater Vehicle, to periodically monitor the seabed bathymetry. Measurements repeated during and after storage activities can be compared with the outcome of numerical simulations and indirectly confirm the existence of safety conditions. To simulate the storage system response to fluid storage, we applied the Virtual Element Method. To illustrate and discuss our methodology, we present a possible application to a depleted gas reservoir in the Adriatic Sea, Italy, where several underground geological formations could be potentially converted into storage in the future.